Sacralizing the Market? The Role of DSN–MUI in the Legal-Economic Legitimacy of Islamic Banking in Indonesia - Fakhrina, Agus; Hamid, Abdul (AHKAM : Jurnal Ilmu Syariah, 2025)
This study explores the complex interplay between religion and economic rationality in the legitimization of Indonesia’s Islamic banking industry. Focusing on the legal authority of the National Sharia Board–Indonesian Ulama Council (DSN–MUI), the research critically examines how fatwas and regulatory accommodations enable Islamic banks to replicate conventional banking practices in pursuit of accelerated growth. Using a qualitative documentary analysis of DSN–MUI fatwas and Indonesia’s banking regulations, the study finds that the DSN–MUI increasingly adopts an accommodative stance by employing istiḥsān bi al-ʿurf wa al-maṣlaḥah (juristic preference based on custom and public interest) to legitimize practices favorable to Islamic banks. While this approach facilitates rapid institutional development, it also raises concerns over the convergence between Islamic and conventional banking models, potentially diluting the normative distinctiveness of Islamic finance. These findings contribute to the broader discourse on Sharia governance, regulatory pragmatism, and the political economy of Islamic finance in Muslim-majority contexts. Abstrak Studi ini menganalisis keterkaitan antara dimensi keagamaan dan rasionalitas ekonomi dalam proses legitimasi industri perbankan syariah di Indonesia. Dengan menitikberatkan pada peran otoritatif Dewan Syariah Nasional–Majelis Ulama Indonesia (DSN–MUI), penelitian ini mengevaluasi secara kritis bagaimana fatwa dan kebijakan regulator digunakan untuk membenarkan praktik-praktik perbankan syariah yang menyerupai sistem konvensional demi mendorong pertumbuhan yang lebih cepat. Melalui analisis dokumen kualitatif terhadap fatwa DSN–MUI dan regulasi perbankan nasional, temuan menunjukkan bahwa DSN–MUI semakin menunjukkan pendekatan akomodatif dengan menggunakan istiḥsān bi al-ʿurf wa al-maṣlaḥah (preferensi hukum berdasarkan kebiasaan dan kemaslahatan) sebagai dasar legitimasi syariah terhadap kebijakan yang mendukung kepentingan bank syariah. Pendekatan ini memang mempercepat perkembangan industri, namun sekaligus menimbulkan kekhawatiran atas semakin hilangnya distingsi normatif antara bank syariah dan bank konvensional. Temuan ini memperkaya wacana kontemporer mengenai tata kelola syariah, kompromi regulatif, dan ekonomi politik keuangan Islam di negara mayoritas Muslim.